2019
DOI: 10.3389/fpsyt.2019.00444
|View full text |Cite
|
Sign up to set email alerts
|

Information Needs of Patients About Immunosuppressive Medication in a German Kidney Transplant Sample: Prevalence and Correlates

Abstract: Background: Worldwide clinical guidelines for the care of kidney transplant (KT) recipients recognize the importance of health care providers imparting appropriate immunosuppressive medication (ISM) information for the facilitation of safe medication self-management. The extent of medication information made available is, however, not necessarily what patients require to know about their prescribed medicines. A useful indicator for determining the quality of prescription practice is to what degree t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 87 publications
(118 reference statements)
1
16
0
2
Order By: Relevance
“…This systematic review discovered that patient needs for education, training, and information have not been sufficiently met [7,17,18,[21][22][23]29,31,35]. Past studies have shown that supporting transplant recipients by increasing their disease-specific knowledge can produce medical and psychological benefits [39].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This systematic review discovered that patient needs for education, training, and information have not been sufficiently met [7,17,18,[21][22][23]29,31,35]. Past studies have shown that supporting transplant recipients by increasing their disease-specific knowledge can produce medical and psychological benefits [39].…”
Section: Discussionmentioning
confidence: 99%
“…Most participants were kidney transplant recipients [7,[15][16][17][18][19][20][21][22][23][24][25][26], followed by heart transplant recipients [5,[27][28][29], liver transplant recipients [30,31], and lung transplant recipients [32]. Three studies were not limited to specific organ transplant recipients [33][34][35].…”
Section: Research Aim and Participantsmentioning
confidence: 99%
See 3 more Smart Citations